Pengaruh Pemberian Tempe Dedak, Tape Dedak dan Kombinasinya Terhadap Perform Ayam Broiler Fase Finisher - Jun, Yuliana; Suryatni, Ni Putu Febri; Sinlae, Markus (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this research is to examine the effect of giving tempe bran tape bran and its combination on the performance of broiler chickens in the finisher period. This research used 96 CP 707 strain broiler chickens aged 21 days. This research method used a Completely Randomized Design with 4 treatments and 6 replications and each replication consisted of 4 broiler chickens. The treatments tried were R0: basal ration + 20 % rice bran (control), R1: basal ration + 20 % tempe bran, R2: basal ration + 20 % tape bran , R3: basal ration + combination of 10 % tempe bran and 10 % tape bran. The variables measured were feed consumption, body weight gain, feed. The results of the study showed that giving tempeh bran, tape bran and their combination had a significant effect (P<0.05) on body weight gain, feed consumption and feed conversion of broiler chickens in the finisher period. It was concluded that the best performance was obtained by broiler chickens that received a combination treatment of 10% tempe bran and 10% tape bran in the ration (R3) in terms of consumption, body weight gain and ration conversion finisher phase broiler chickens.